The Mechanism of Mind : Understand How Your Mind Works to Maximise Memory and Creative Potential - De Bono, Edward (London Vermilion of Penguin Random House, 2015)
It explains why the brain, the 'mechanism', can only work in certain ways and introduces the four basic types of thinking that have gone on to inform his life's work, namely `natural thinking', `logical thinking',' mathematical thinking' and `lateral thinking'.
Include Illustrations and Graphs
Keywords: Mnemonics -- Creative thinking